The Role of Contactin 1 in Cancers: What We Know So Far - Liang, Yumei; Ma, Cui; Li, Fengjuan; Nie, Guanhua; Zhang, Haining (Frontiers in Oncology, 2020)
Cancers are amongst the difficult to treat diseases, despite advances in diagnosis and treatment. Although newer effective targets remain to be discovered, targeted therapy has emerged as a promising field. In the last decade, contactin 1 (CNTN1) has surfaced as an important cancer-related molecule. CNTN1 is a neuronal membrane glycoprotein, which if overexpressed is found in different cancer cell lines, cancer tissues, and transgenic mice. It is positively associated with lymphatic invasion, metastasis, late TNM stage, and a short overall survival time. However, the role of CNTN1 in cancer cell proliferation remains unclear. In addition, CNTN1 is involved in cancer cell invasion, migration, metastasis, and chemoresistance by promoting epithelial-mesenchymal transition, and mediating several signal transduction pathways. Several studies suggested CNTN1 as a new therapeutic target for cancers. This review aimed to summarize the research developments on CNTN1 in various cancers, to establish its role in epithelial-mesenchymal transition and signal transduction pathways, and to identify promising areas for further investigations.